Dynamic behavior of the submerged floating tunnel moored by inclined tethers attached to fixed towers. (1st October 2021) - Won, Deokhee; Park, Woo-Sun; Kang, Young Jong; Kim, Seungjun
Abstract: To develop an optimum design concept for the submerged floating tunnel (SFT), many studies have evaluated the dynamic behavioral characteristics of submerged structures under various design loads and it has been concluded that rational mooring systems should be applied to very large and long submerged structures for use as transportation facilities. For this purpose, the concept of SFTs moored by laterally inclined tethers anchored to the seabed has been mainly studied. However, the issue of erecting many tethers with individual seabed anchors or piles should be solved for the mooring systems. This study aims to investigate the feasibility of the SFTs moored by inclined tethers attached to fixed towers. The new concept of SFTs, which fundamentally originated from cable-stayed bridges, was proposed for reducing burden of construction of individual seabed piles for each tether. In this study, behavioral characteristics of the SFT under the regular and irregular waves were investigated by performing hydrodynamic analysis in time-domain. For suggesting feasible and acceptable concepts for the transportation facilities, the effects of various geometric design parameters, such as the draft, sectional characteristics of the tunnel, stiffness of the tethers, and inclination of the fixed tower legs on the structural behaviors have been evaluated. Highlights: The structural behaviors of the newly suggested SFT model are investigated by hydrodynamic analysis in the time domain. Case studies are conducted to investigate the effects of design parameters on structural performances of the suggested SFT. Application of deep-draft submerged tunnels and high stiffness tethers are effective to reduce the dynamic responses of SFT. The dual-tube type SFT could be one of the alternative concepts for the harsh environment. The design engineer should carefully combine the design strategies to reduce the structural responses of the SFT.